Characterisation of lactic acid bacteria from Turkish sourdough and determination of their exopolysaccharide (EPS) production characteristics - Dertli, Enes; Mercan, Emin; Arici, Muhammet; Yilmaz, Mustafa Tahsin; Sagdic, Osman (ELSEVIER, 2016)
A total of 249 Lactic Acid Bacteria (LAB) isolates were found in traditional Turkish wheat sourdoughs from Eastern Black Sea region of Turkey. Genotypic characterization of these isolates revealed the presence of 47 distinct LAB strains belonging to 11 different species: Lactobacillus plantarum, Lactobacillus paraplantarum, Lactobacillus curvatus, Lactobacillus rossiae, Lactobacillus sanfranciscensis, Lactobacillus brevis, Lactobacillus paralimentarius, Weissella paramesenteroides, Leuconostoc mesenteroides, Leuconostoc pseudomesenteroides and Weissella cibaria. The sourdough LAB microbiota differed depending on the sample origin and the collection period and heterofermentative LAB were dominant. The number of different species within a sourdough varied from 3 to 6 with the association of different hetero- and homofermentative LAB species. Exopolysaccharide (EPS) production characteristics of the isolates were determined and strain specific properties appeared to be important for the final EPS yields. Genes required for homopolysaccharide (gtf and lev) and heteropolysaccharide (epsA, epsB, p-gtf) production were PCR detected and several distribution patterns were observed. Results of this study confirmed the biodiversity of LAB species in traditional Turkish sourdough and highlighted the importance of EPS production in sourdough LAB strains. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Sourdough; Lactic acid bacteria (LAB); Microbial biodiversity; Exopolysaccharides (EPS); LACTOBACILLUS-SANFRANCISCENSIS; MOLECULAR CHARACTERIZATION; WEISSELLA-CIBARIA; WHEAT SOURDOUGH; IDENTIFICATION; BIOSYNTHESIS; BIODIVERSITY; FERMENTATION; STARTERS; FLOURS; Food Science & Technology